1986
DOI: 10.1002/jat.2550060404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of urinary flow on adjusted and non‐adjusted excretion of heavy metals and organic substances in ‘healthy’ men

Abstract: The effect of variation in urinary flow rate (ml urine min-1, UF) on adjusted and non-adjusted urinary excretion of metals and organic substances was examined in ten 'healthy' men. The effect of UF was found to be eliminated when urinary concentrations of lead (Pb), hippuric acid (HA), delta-aminolevulinic acid (ALA) and coproporphyrin (CP) were adjusted to urinary specific gravity and to UF. Similarly, the effect of UF on inorganic mercury (Hg) was eliminated when the concentration was adjusted to timed excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
2
10
2
Order By: Relevance
“…1 ) significant ( p < 0.001) negative, log-linear relationships with UFR. This confirmed previous findings [ 20 ]. The weak (Pb, Cd, As IMM and I in Fig.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…1 ) significant ( p < 0.001) negative, log-linear relationships with UFR. This confirmed previous findings [ 20 ]. The weak (Pb, Cd, As IMM and I in Fig.…”
Section: Resultssupporting
confidence: 94%
“…hydration, at that time. Strong positive Spearman’s correlation coefficients (r s ) have been reported between ERs of urinary analytes and UFR [ 20 , 21 ], indicating that the adjustment in Eq. 2 is not theoretically robust.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The requirements of users of such assays are rather different from those of a woman monitoring her own fertility every day. In other cases, such as the monitoring of heavy metal exposure by urinalysis, not only is correction advocated, but it is demonstrated that the best means of achieving this is to correct using the urine production rate (Araki et al, 1986a;Araki et al, 1986b;Weaver et al, 2014). We have shown previously that urine production rate correction of E1G concentrations is necessary if the intention is to obtain an estimate of the corresponding serum analyte concentration (Brown et al, 2018).…”
Section: Discussionmentioning
confidence: 99%